A Comparative Clinical Study Of Rasnadi Guggulu And Trayodashanga Guggulu In The Management Of Sandhigata Vata(Related To Janu Sandhi) W.S.R To Osteoarthritis - Mohan, G Vinay; Rudrapuri, Mahantesh B; Dharmannavar, Girish S; Deepika, G (International Research Journal of Ayurveda & Yoga, 2020)
Sandhigata vata is described under vatavyadhi in all Samhitas and sangrahagranthas. It mainly occurs in vriddavastha due to Dhatukshaya, which limits the day to day activities like walking, dressing etc thus making patient disabled. It being a vatavyadhi, located in marmasthisandhi and mainly occur in vriddavasta makes it kastasadya. Here vata dosha plays a main role to cause disease. The sandhigata vata is characterized by pain, swelling and restricted movement of joints. When Sandhi vata occurs in knee joint(janu sandhi), it is called Janu sandhigata vata. These clinical findings show a similarity with osteoarthritis of contemporary science. Hence the drugs Rasnadiguggulu and Trayodashangaguggulu which has the properties of shoolahara ,shotahara and rasayana are taken for the study. So the present study was undertaken “To compare the efficacy of the Rasnadiguggulu and Trayodashangaguggulu as shamana- oushadi in sandigata vata as claimed in Yogaratnakara and chakradatta.For the present study, 40 patients with age limit 40-70 years were diagnosed as a sandigatavata were selected from Shri Shivayogeeshwar Rural Ayurvedic Medical College and Hospital , Inchal , selected patients were systematically arranged to 2 groups. Group-A patients received Rasnadiguggulu 450mg 2 tab twice a day with sukoshnajala as anupana for 30 days and Group- B patients received Trayodashangaguggulu 450mg 2 tab twice a day with sukoshnajala as anupana for 30 days. The patients were assessed for the severity of the disease subjectively and objectively before, during and after the treatment. At the end of the follow up, the data from each group were statistically analyzed and were compared. Significant results were obtained in relieving the symptoms of Sandhigata vata (related to Janu sandhi) by the end of the treatment period in both the groups. Overall assessment showed marked, moderate and mild improvement in the patients. From the clinical study, it was evident that all patients responded to the treatment. Comparative analysis of the overall effects of treatments in both group showed that the treatment is statistically significant in Group-B when compared to Group-A.